2022
DOI: 10.3389/fcell.2021.794801
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of m6A Regulator-Mediated Methylation Modification Patterns and Tumor Microenvironment Infiltration in Ovarian Cancer

Abstract: Introduction: Studies have demonstrated the epigenetic regulation of immune responses in various cancers. However, little is known about the RNA N6-methyladenosine (m6A) modification patterns of the microenvironment (TME) cell infiltration in ovarian cancer (OC).Methods: We evaluated the correlation between m6A modification patterns and TME cell infiltration based on 459 OC samples from the Cancer Genome Atlas and Gene-Expression Omnibus database. We constructed an m6Ascore system to quantify m6A modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Whether this effect also exists in ovarian cancer, as well as other neoplasm of reproductive system, is worth further exploration. Also, Luo et al [56] found m6A affected the process of antigen presentation in the immune system and played an important role in TME cell infiltration in OC. Some m6A protein machineries and methylated gene loci have been found in OC, which may be used as therapeutic targets or prognostic markers in the future.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Whether this effect also exists in ovarian cancer, as well as other neoplasm of reproductive system, is worth further exploration. Also, Luo et al [56] found m6A affected the process of antigen presentation in the immune system and played an important role in TME cell infiltration in OC. Some m6A protein machineries and methylated gene loci have been found in OC, which may be used as therapeutic targets or prognostic markers in the future.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In terms of ovarian OCs, a study demonstrated m1A modifications played critical roles in tumor immune microenvironment formation and prognosis of OC patients ( 51 ). Identically, m6A modification was proved to play an essential part in tumor microenvironment cell infiltration in OCs ( 52 ). This present study further analyzed the relationship of OC subtypes and immune types.…”
Section: Discussionmentioning
confidence: 99%
“…32 To depict the CNV landscape of the 21 m6A regulators across 23 chromosome pairs, we used the “RCircos” R package for visualization. 33,34…”
Section: Methodsmentioning
confidence: 99%
“…For evaluating prognosis, the Univariate Cox regression model was applied to each m6A gene signature, identifying genes with noteworthy prognostic implications. Principal component analysis (PCA) was then employed to construct the m6A-related gene signature, 34 using i as the m6A phenotype-associated genes' expression…”
Section: Generation Of M6a Scorementioning
confidence: 99%